Crash - Haggis, Paul; Schulman, Cathay; Bullock, Sandra; Lions Gate Films; Bob Yari Productions; DEJ Productions ([Santa Monica, Calif.] : Lion Gates Films)
A car accident brings together a group of strangers in Los Angeles. Crash takes a provocative, unflinching look at the complexities of racial tolerance in contemporary America. This compelling urban thriller tracks the volatile intersection of a multiethnic cast of characters struggling to overcome their fears as they careen in and out of one another's lives
Title from title screen
Subtitles in English and Spanish
Story by Paul Haggis ; screenplay by Paul Haggis & Bobby Moresco ; director of photography, J. Michael Muro ; editor, Hughes Winborne ; music, Mark Isham ; costume designer, Linda Bass ; production designer, Laurence Bennett
Casts: Sandra Bullock, Don Cheadle, Matt Dillon, Jennifer Esposito, William Fichtner, Brendan Fraser, Terrence Howard, Chris'Ludacris' Bridges, Thandie Newton, Ryan Phillippe, Larenz Tate
Keywords: Racism -- California -- Los Angeles -- Drama; Traffic accidents -- California -- Los Angeles -- Drama